Phytochemical and antibacterial screening of different fractions of root part of Ipomea Turpethum (Bangladesh Journal of Medical Science, 2018)
Objective: In folk medicines, different herbs and plants have been used for many thousands of years .Now it is important to investigate these plants and herbs scientifically which have been used in traditional medicines. The aim of this study was to investigate the antibacterial activity and preliminary phytochemical screening of root of Ipomea turpethum extracted in methanol and its fractions.Methods: The methanol extract was further extracted with three solvents ethyl acetate, chloroform and hexane and analyzed for their antibacterial activity using by agar well diffusion method. They were tested against six bacteria; Echrichia coli, Staphylococcus aureus, Staphylococcus epidermidus, Proteus vulgaris, Pseudomonas auroginosa and Salmonella typhi. The susceptibility of microorganisms to all three fractions was compared with each other and with standard antibotic (Ampicillin). The fractions of Ipomea turpethum was also qualitatively analyzed for the presence of chemical components, i.e. saponins, alkaloids, flavonoids, tannins and glycosides.Result: Among all fractions methanol exhibited highest antibacterial activity (average zone of inhibition 23.53mm ± 1.3) while ethyl acetate exhibited least antibacterial activity (average zone of inhibition 18.50mm ± 3.5). Minimum inhibitory concentration of methanol, ethyl acetate, chloroform and hexane fractions was found in the range of 650ug/ml to 2500ugl/ml against microorganisms.Conclusion: Results obtained from this preliminary in-vitro experiment indicate that, all three fractions of Ipomea turpethum has good antibacterial activity against all microorganisms used. By phytochemical analysis of extract, it has been found to contain some nutrient and chemical components which support its ethenomedicinal use but further work is required for development of new antibiotic compounds.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.93-97